1995
DOI: 10.1172/jci118312
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin induction of PAI-1 expression in endothelial cells is mediated by the hexapeptide angiotensin IV.

Abstract: Recent studies from this laboratory have demonstrated that angiotensin TT (Ang II) stimulates the expression of plasminogen activator inhibitor 1 (PAI-1) in cultured endothelial cells. This response does not appear to be mediated via an interaction with either the AT, or the AT2 receptor subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
157
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(167 citation statements)
references
References 30 publications
3
157
1
6
Order By: Relevance
“…AT 1a and AT 1b exhibit similar ligand binding and signal transduction properties, and cannot be distinguished pharmacologically, but differ in their tissue distribution. 3 In addition to Ang II, shorter Ang metabolites, such as Ang IV 4,5 and Ang-(1-7), [6][7][8] demonstrate potent biological activity. The heptapeptide Ang-(1-7) is an Ang metabolite of special interest because it can often counteract the detrimental effects of Ang II, for example, its vasoconstrictive properties.…”
Section: Introductionmentioning
confidence: 99%
“…AT 1a and AT 1b exhibit similar ligand binding and signal transduction properties, and cannot be distinguished pharmacologically, but differ in their tissue distribution. 3 In addition to Ang II, shorter Ang metabolites, such as Ang IV 4,5 and Ang-(1-7), [6][7][8] demonstrate potent biological activity. The heptapeptide Ang-(1-7) is an Ang metabolite of special interest because it can often counteract the detrimental effects of Ang II, for example, its vasoconstrictive properties.…”
Section: Introductionmentioning
confidence: 99%
“…9 In contrast, other reports have suggested that the AT 1 receptor does not mediate Ang II-stimulated PAI-1 expression. 24,25 Establishing the role of the AT 1 receptor in the regulation of PAI-1 expression may have important clinical significance related to potential differences between ACE inhibitors and AT 1 antagonists on the fibrinolytic system.…”
mentioning
confidence: 99%
“…10,11 The dissimilar effects of imidapril and candesartan on PAI-1 could have been due in part to increased PAI-1 expression by the hexapeptide Ang II metabolite Ang IV and to stimulation of AT4 receptor, as reported in vitro in human endothelial cells. 52 These effects could have increased PAI-1 antigen concentration after short-term AT1 receptor blockade and after 2 week AT1 blockade, when AT4 receptors may be upregulated. 53 This mechanism is difficult to determine in a clinical setting and remains undetermined in the present study.…”
Section: Discussionmentioning
confidence: 99%